SISTEM PAKAR DIAGNOSA PENYAKIT TANAMAN SELEDRI DENGAN METODE FORWARD CHANING DI KELOMPOK TANI DESA SIAMPORIK: Forward chaining - Jalampiran Pasaribu, Putri delviana; Kusmanto; Munthe, Shabrina Rasyid (U-NET Jurnal Teknik Informatika, 2024)
This research is motivated by problems in Siamporik Village who have good celery planting skills, but lack knowledge about this celery plant disease. In the village of Siamporik, the skill of growing celery is due to the lack of detecting celery disease which makes the harvest unsatisfactory. To reduce yield losses, an expert system for diagnosing sop leaves (celery) was created so that it can detect plant diseases, using the Forward Channeling method, using the Web as an application, and using MySQL and Xampp databases.